Evaluating changes in electronic gambling machine policy on user losses in an Australian jurisdiction - Matthew Stevens; Charles Livingstone (BMC, 2019)
Abstract Background Electronic gambling machines (EGMs) are in casinos and community venues (hotels and clubs) in all jurisdictions in Australia, except Western Australia (only in casino). EGMs have a range of features that can affect how people gamble, which can influence losses incurred by users. The Northern Territory Government recently changed two EGM policies - the introduction of note acceptors on EGMs in community venues, and an increase in the cap from 10 to 20 EGMs in hotels and 45 to 55 in clubs. This study evaluates two changes in EGM policy on user losses in community venues, and tracks changes in user losses per adult, EGM gambler, and EGM problem/moderate risk gambler between 2005 and 2015. Methods Trends in venue numbers, EGM numbers, user losses and user losses per EGM by venue type and size are presented to determine if EGM policy changes affected user losses. Data from the 2005 and 2015 NT gambling surveys are used to determine EGM user losses per adult, per EGM gambler, and per EGM problem and/or moderate risk gambler, with several assumptions applied. Results From 2010 (post smoking ban) to 2013 real user losses were stagnant, but from 2013 to 2017, real user losses in community venues increased 19, 9, 8 and 5% per annum, with increases higher in clubs and hotels with the maximum allowable number of EGMs. Over the same period user losses in the two casinos declined by 13%. Between 2005 and 2015, estimated user losses per EGM problem/moderate risk and problem gambler increased by 5 and 34% respectively. Conclusions The analysis demonstrates that reductions in how much money gamblers can insert into an EGM (load-up limit), and/or the abolition of note acceptors, and reductions in the number of EGMs in venues is likely to reduce harm from EGM use. Given the demonstrated inability for Australian jurisdictions to identify and implement effective harm prevention and minimisation interventions, a national approach to gambling regulation in Australia may be desirable. Similarly, national co-ordination of research, particularly on EGMs and online betting is required to better understand changes in gambling policy on related harms.